Prealgebra (7th Edition)

Published by Pearson
ISBN 10: 0321955048
ISBN 13: 978-0-32195-504-3

Chapter 4 - Review - Page 321: 80



Work Step by Step

$\frac{\frac{5}{6}-\frac{1}{4}}{\frac{-1}{12y}}$ $=(\frac{5}{6}-\frac{1}{4})\div(\frac{-1}{12y})$ $=(\frac{5\times2}{6\times2}-\frac{1\times3}{4\times3})\div(\frac{-1}{12y})$ $=(\frac{10}{12}-\frac{3}{12})\times(\frac{12y}{-1})$ $=(\frac{7}{/\!\!\!12})\times(\frac{/\!\!\!12y}{-1})$ $=\frac{7y}{-1}$ $=-7y$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.